Coral reef fishes in the banks and rocky islands in the offshore waters of Binh Thuan province - Dat, Mai Xuan (Vietnam Journal of Marine Science and Technology, 2019)
Binh Thuan province is located in the South Central Coast of Vietnam with favorable conditions for living coral reefs. The coral reefs were mainly investigated in coastal water areas and Phu Quy island, meanwhile other areas such as the banks and rocky islands seem to lack information. This study was conducted to evaluate the species composition and distribution of coral reef fish communities in the Royal Bishop banks and around rocky islands in Julia shoal in the offshore waters of Binh Thuan province in April 2019. A total of 151 species belonging to 86 genera and 33 families of coral reef fishes were recorded. Among them, 4 species for the first time recorded in Vietnam are Helcogramma striata (Hansen, 1986) (Tripterygiidae), Pseudanthias squamipinnis (Peters, 1855) (Serranidae), Bodianus bilunulatus (Lacepède, 1801) and Coris aygula (Lacepède, 1801) (Labridae). The total average density of coral reef fish in the offshore waters of Binh Thuan is quite high at 1,104.9 ± 617 individuals/250 m2, most of them are small sized fish and ornamental fish group, the large sized fish and target fish group accounts for a relatively low rate, but their density here is much higher compared to that in the coastal waters of Binh Thuan province. The comparative analysis also shows that sites in coral reef around rocky islands have species richness and density of coral reef fish higher than the bank area